The Internet of Things: Typologies, Protocols and Applications - Pataca, Campos (Law, State and Telecommunications Review, 2021)
[Purpose] The purpose of the article is to characterize the internet of things in its diversity of terminological approach, base of protocols, technological information and main applications. [Methodology] The article communicates the bibliographic research on the theme, in an exploratory descriptive study approach. From the bibliographic research it was possible to identify the different typologies of the internet of things and to establish the conceptual differences and specificities, both technological and their application. [Findings] The article goes through an analysis of the evolution of the web, establishing the precise link of the emergence of the internet of things in web 3.0. It establishes the specific difference between the internet of things and the internet of everything in terms of the basic pillars of interaction. While the range of applications highlights five main domains: domestic, social, environmental, technological and emergency. [Practical Implications] The article has an evident application to characterize the stack of specific communication and security protocols, in addition to the common ones of the internet. It can also provide the different actors with the appropriate options for the desired applications according to the specificities. [Originality] The article features nineteen specific types of internet of things in a single documentary text and a synthesis of applications grouped into areas or domains.